(untitled) (Revista Latino-Americana de Enfermagem, 2012)
AIM: identify and analyze in the literature the evidence of randomized controlled trials on care related to the suctioning of endotracheal secretions in intubated, critically ill adult patients undergoing mechanical ventilation. METHOD: the search was conducted in the PubMed, EMBASE, CENTRAL, CINAHL and LILACS databases. From the 631 citations found, 17 studies were selected. RESULTS: Evidence was identified for six categories of intervention related to endotracheal suctioning, which were analyzed according to outcomes related to hemodynamic and blood gas alterations, microbial colonization, nosocomial infection, and others. CONCLUSIONS: although the evidence obtained is relevant to the practice of endotracheal aspiration, the risks of bias found in the studies selected compromise the evidence's reliability.